Negative Hydrogen Ion Sources for Fusion: From Plasma Generation to Beam Properties - Fantz, U.; Briefi, S.; Heiler, A.; Wimmer, C.; Wünderlich, D. (Frontiers in Physics, 2021)
The neutral beam injection systems for ITER used for heating, current drive and diagnostic purposes are based on RF-driven negative hydrogen ion sources with a source area of roughly 0.9 m × 1.9 m. The sources operate at 0.3 Pa in hydrogen and in deuterium using a total available RF generator power of 800 kW per source at a frequency of 1 MHz. In order to fulfil the challenging requirements for ITER and beyond (like a DEMOnstration power plant, DEMO) worldwide developments are underway addressing the topics of plasma generation, ion extraction together with the issue of reducing and stabilizing the co-extracted electron current, and the beam properties. At the example of the activities at the ITER prototype source and the size scaling experiment ELISE, the present status and its challenges are summarized. The RF power transfer efficiency of these sources is only about 65% in maximum giving significant room for improvements to relax the demands on the RF generator and ensure reliable operation. The plasma uniformity in front of the large extraction system is the result of plasma drifts. They have a huge impact on the non-uniformity of the co-extracted electrons and influence the ions and thus the beam properties as well. Understanding the optics of such large beams composed of hundreds of beamlets is a crucial task and under continuous improvement. The main challenge, however, is still the fulfilment of the ITER requirements for deuterium, in particular in long pulses. The management of caesium, which is evaporated into the source to generate sufficient negative ions by the surface conversion process, is one of the keys for stable and reliable operation